A Sociolinguistic Analysis of Taboo and Swear Word in Deadpool: A Movie by Tim Miller - Premi Septi Lestari; Asridayani Asridayani; Vera Magria (Krinok:Jurnal Linguistik Budaya, 2019)
This thesis analyzes about taboo and swear words in Deadpool movie using sociolinguistic approach. The purposes of this research are to analyze and explain types of taboo and swear words, functions of taboo and swear word, and reasons for using taboo and swear word. In analyzing the research, the writer uses sociolinguistic and some supporting theories. The method used in this research is descriptive qualitative. The data is formed in wordsand pictures. The data is analyzed through four procedures: identifying, classifying, analyzing and making conclusion. The results of this research are stated as follows. Firstly, four types of taboo words occur in the characters’ utterances in Deadpool movie; epithet, profanity, vulgarity, and obscenity. While for swear word, the type that dominant in the movie is private parts of body. In the function of taboo word, the writer only finds three from four functions. Then, for the reason of using taboo and swear word, the writer finds psychology and social class. The writer finds the correlation between taboo words and swear words. Keywords : Sociolinguistic, Taboo Word, Swear Word, and Deadpool movie